Provision of adolescent health care in Resource-Limited Settings: Perceptions, practices and training needs of Ugandan health care workers. (January 2022) - Miller, Kathleen K.; Saftner, Melissa A.; McNamara, Meredithe; McMorris, Barbara; Olupot-Olupot, Peter
Highlights: Health care workers (HCWS) in eastern Uganda identified adolescent immunization and HIV prevention as priorities in adolescent health. HCWs acknowledged discomfort and lack of experience in the provision of contraception and non-HIV testing for sexually transmitted infections for adolescents. HCWs demonstrated conflicting perspectives on the appropriateness of contraceptive for unmarried adolescents, with roughly half expressing concerns that contraception may not be appropriate for unmarried adolescents. 96% of participants expressed interest in obtaining additional training in adolescent health. Abstract: Adolescent health is increasingly recognized as a global priority. However, gaps exist in training in adolescent health for frontline health care workers (HCWs) in low- and middle-income countries (LMICs). This mixed methods study utilized data from focus groups and quantitative surveys to better understand the perceptions, practices, and training needs of HCWs who provide care to adolescents in eastern Uganda. Focus group discussions (FGD) were conducted with thirty-six HCWs, who demonstrated a nuanced understanding of the specific health care needs of adolescents, citing HIV care and HPV vaccination as priorities, and indicating comfort in the provision of these services. Quantitative results indicated less comfort with contraception and safe sex counseling, as well as treating mental health and addiction problems. In focus groups, HCWs were divided as to whether or not unmarried adolescents should be able to access essential components of reproductive healthcare, including contraception and non-HIV testing for sexually transmitting infections (STIs). Most agreed that HIV testing and treatment should be offered to all adolescents. HCWs also acknowledged the challenges of delivering culturally appropriate care amidst societal stigma regarding sexual health. Additional challenges in adolescent care include limited resources, lack of standard practices for providing confidential care, and limited training in adolescent development. There is a need for further discussion and training among HCWs to increase their comfort level in providing care for adolescents, and the majority of participants in this study (96%) were interested in obtaining this additional training.